Safety Stressors and Construction Workers' Safety Performance: The Mediating Role of Ego Depletion and Self-Efficacy - Ye, Gui; Xiang, Qingting; Yang, Lijuan; Yang, Jingjing; Xia, Nini; Liu, Yang; He, Tiantian (Frontiers in Psychology, 2022)
As an important influencing factor of construction workers’ safety performance, safety stressor has received increasing attention. However, no consensus has been reached on the relationship between different types of safety stressors and the subdimensions of safety performance, and the mechanism by which safety stressors influence safety performance remains unclear. This study proposed a multiple mediation model with ego depletion and self-efficacy as mediators between safety stressors and workers’ safety performance. Data were collected from 335 construction workers in China. Results demonstrated that: (1) the three type of safety stressors (i.e., safety role ambiguity, safety role conflict and interpersonal safety conflict) all had negative effects on workers’ safety performance (i.e., safety compliance and safety participation); (2) self-efficacy mediated all the relationships between the three safety stressors and safety performance; (3) ego depletion only mediated part of the relationships between the three safety stressors and safety performance; and (4) only part of the multiple-step mediating effects through ego depletion and self-efficacy were supported. This study makes contributions by shedding lights on the mechanism by which safety stressors influence workers’ safety performance and providing more empirical evidence for the relationship between various safety stressors and the subdimensions of safety performance. Additionally, targeted strategies for improving workers’ safety performance were proposed according to the findings.